Clickable polyurethanes based on s- triazine ring containing aromatic diisocyanate bearing pendent alkyne group: synthesis and postmodification - Garg, Kavita; Chatterjee, Deepshikha; Wadgaonkar, Prakash (Journal of Polymer Science Part A Polymer Chemistry, 2017)
A new s-triazine ring containing aromatic diisocyanate bearing a pendent alkyne group, namely, 2,4-bis(4-isocyanatophenoxy)−6-(prop-2-yn-1-yloxy)−1,3,5-triazine was synthesized and reacted with various diols viz., 1,10-decanediol, tetraethylene glycol and polyethylene glycols in the presence of dibutyltin dilaurate as the catalyst to obtain a series of linear polyurethanes. The selected polyurethanes possessing pendent alkyne groups were postmodified with chemically diverse azides viz., 1-(azidomethyl)benzene, 1-(azidomethyl)pyrene, and methoxy end-caped poly(ethylene glycol) azide via copper-catalysed azide-alkyne Huisgen 1,3-dipolar cycloaddition. FTIR and 1H NMR spectra indicated quantitative click reaction. UV–vis and fluorescence spectroscopic analysis confirmed complete incorporation of pyrenyl groups indicating the formation of fluorescence active polyurethane by postmodification with 1-(azidomethyl)pyrene. TG analysis of polyurethanes indicated two stage weight loss and their thermal stability, as judged by T10 values, was governed by weight percent of urethane linkages. The water contact angle measurements revealed improved wettability with increased content of PEG either in the backbone of polyurethanes or as grafted chains. DLS and TEM studies confirmed that certain polyurethanes possessing PEG segments displayed self-assembly in aqueous solution, which was further supported by pyrene encapsulation studies using UV–vis spectroscopy. © 2017 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem. 2017, 55, 1008–1020
Keywords: Click chemistry; Diisocynate; Polyethelene Glycol; polyurethanes; Self- Assembly

Step-growth polymers from cashew nut shell liquid (CNSL)-based aromatic difunctional monomers - Chatterjee, Deepshikha; Sadavarte, Nilakshi V.; Shingte, Rahul D.; More, Arvind S.; Tawade, Bhausaheb V.; Kulkarni, Arun D.; Ichake, Amol B.; Avadhani, C. V.; Wadgaonkar, Prakash P. (Cashew Nut Shell Liquid, 2017)
Cashew nut shell liquid (CNSL) is an attractive renewable resource material which is available in abundance (44,50,000 tonnes worldwide and 7,53,000 tonnes in India in 2013) at low cost (around 0.27 $/kg in 2015) and is mainly composed of anacardic acid, cardanol, cardol and 2-methyl cardol. Cardanol is obtained as a major product during hot oil extraction or roasting process of CNSL. Cardanol possesses interesting structural features. The aromatic ring of cardanol can undergo electrophilic substitution reactions; the unsaturated side chain can undergo epoxidation, hydrogenation, metathesis, etc., while the phenolic hydroxyl group can undergo various reactions such as esterification and alkylation. Such opportunities of chemical modifications offered by cardanol have been extensively explored to synthesise a range of interesting aromatic difunctional monomers that have subsequently been utilised to prepare a host of step-growth polymers. Summarised herein are research efforts that have contributed towards the synthesis of step-growth polymers based on aromatic difunctional monomers derived from cardanol. The properties of high-performance polymers, with a particular focus on processability and thermal characteristics, are highlighted.

Partially bio-based triarylamine-containing polyimides: synthesis, characterization and evaluation in non-volatile memory device applications - Chatterjee, Deepshikha; Jadhav, Uday A.; Javaregowda, Bharathkumar H.; Dongale, Tukaram D.; Patil, Pramod S.; Wadgaonkar, Prakash P. (European Polymer Journal, 2021)
A new triarylamine-containing diamine, viz. 4, 4'-diamino-4 `' pentadecyltriphenylamine was synthesised starting from cashew nut shell liquid (CNSL) - a non-edible by-product of cashew processing industry. Three new partially bio-based triarylamine-containing polyimides were synthesised by one-step high temperature solution poly-condensation of 4, 4'-diamino-4 `' pentadecyltriphenylamine with aromatic dianhydrides, namely, 3,3',4,4'-biphenyltetracarboxylic dianhydride (BPDA), 4,4'-oxydiphthalic anhydride (ODPA) and 4,4'-(hexa-fluoroisopropylidene) diphthalic anhydride (6-FDA). Polyimides were determined to be of reasonably high molecular weights as inherent viscosity and number average molecular weights (M-n, Polystyrene standard) values were in the range 0.54-0.60 dL g(-1) and 26,800-43,500 g mol(-1), respectively. Polyimides exhibited excellent solubility in common organic solvents and film-forming nature along with reasonably good thermal properties as indicated by temperature for 10% weight loss (T-10) and glass transition temperatures (T-g) which were in the range 418-447 and 165-225 degrees C, respectively. The optical and electrochemical band-gap values were in the range of 1.95-1.98 eV and 1.671-1.745 eV, respectively. Among triarylamine-containing polyimide devices, BPDA-based device showed acceptable current-voltage and non-volatile memory properties such as the endurance of 500 cycles and 1000 s of retention time. The conduction mechanism developed in the memory devices was also explored and was found to follow Ohmic and Schottky conduction mechanisms.
Keywords: Bio-based polyimides; CNSL; Memory device; pentadecyl; Triarylamine